2001
DOI: 10.1055/s-2001-19026
|View full text |Cite
|
Sign up to set email alerts
|

Interventionelle ERCP bei Patienten mit Cholestase: Häufigkeit und Antibiotikaresistenz der biliären Keimbesiedlung

Abstract: Interventional ERCP in patients with cholestasis. Degree of biliary bacterial colonization and antibiotic resistance. Biliary obstruction together with bacterial colonization of the bile duct may lead to development of acute cholangitis. The aim of our prospective study was to investigate the presence and degree of biliary bacterial colonization by means of bile aspiration during ERCP in patients with biliary obstruction. Furthermore, we evaluated antibiotic therapy regimens, which would cover the bacterial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…In comparison to other studies, the high positivity of bile culture in our population was due to prolonged stasis of bile prior to ERCP, because the most common indication for ERCP in our patients was CBD stricture followed by CBD stone. There are other studies reporting variable bile culture positivity rates in different populations, ranging from 16% to 85% [9,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other studies, the high positivity of bile culture in our population was due to prolonged stasis of bile prior to ERCP, because the most common indication for ERCP in our patients was CBD stricture followed by CBD stone. There are other studies reporting variable bile culture positivity rates in different populations, ranging from 16% to 85% [9,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, E. coli was the most frequent isolate while Enterococcus was the most common Gram-positive sample [21]. Other independent studies reported 16% to 85% positive bile culture among different disease groups [14, 15, 17, 2225].…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten mit biliärer Obstruktion besteht in ca. 10 % der Fälle die zusätzliche Gefahr einer Infektion mit anaeroben Keimen [1]. Deshalb wurde in beiden Therapiearmen Metronidazol 1,5 g/die ergänzt.…”
Section: Methodeunclassified
“…Die häufigsten Keime der akuten Cholangitis sind E. coli, Enterokokken und Klebsiellen. Bei der In-vitro-Resistenztestung verschiedener biliärer Keimgemische wies Levofloxacin die niedrigsten Resistenzraten in einer Voruntersuchung auf [1].…”
Section: Introductionunclassified